2011
DOI: 10.1016/j.transproceed.2010.12.039
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Cancer and Potential Role of Sirolimus Immunosuppression Conversion on Mortality Among a Single-Center Renal Transplantation Cohort of 1,816 Patients

Abstract: Introduction. The chronic use of immunosuppressive drugs in renal transplant recipients increases the risk of developing de novo malignancies. Herein we analyze the incidence of de novo tumors and the potential role of sirolimus to improve cancer-specific survival among a cohort at a single center.Methods. This retrospective analysis of our 1,816 patients allografted between January 1983 and December 2009 sought subjects who developed de novo tumors. Epidemiological and clinical data were examined using Mann-W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It has therefore been the focus of interest in the treatment of malignancy [46,47]. It has been shown to inhibit the progression of Kaposi's sarcoma in renal transplant patients [48] and is the subject of current interest to see if it can have a similar effect in urogenital tumours [49]. Due to the few patients within each centre, collaborative research may be required to answer that hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has therefore been the focus of interest in the treatment of malignancy [46,47]. It has been shown to inhibit the progression of Kaposi's sarcoma in renal transplant patients [48] and is the subject of current interest to see if it can have a similar effect in urogenital tumours [49]. Due to the few patients within each centre, collaborative research may be required to answer that hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the blood trough level of sirolimus was maintained between 5 and 15 ng/mL, based on a previous phase 1–2 trial [ 9 ]. However, the optimal treatment dose was not given because a significant number of patients developed problematic side effects, such as stomatitis, and the potential risk of developing a malignant tumour increased with long-term use [ 12 ]. In a recent study, low-dose sirolimus treatment (trough level < 5 ng/mL) was shown to improve lung function in nine patients without chylous effusion and to resolve chylothoraxes in seven patients with chylous effusions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors suggest the introduction of mammalian target of Rapamycin inhibitors after solid organ cancer in LTRs. Vallin et al [19] and Branco et al [20] in prospective studies failed to show a real benefit of everolimus-based immunosuppression in LTRs. Many adverse effects were reported such as hypercholesterolemia, renal toxicity, mucositis, edema, and hematotoxicity.…”
Section: Discussionmentioning
confidence: 98%